DC-derived IL-18 drives Treg differentiation, murine Helicobacter pylori-specific immune tolerance, and asthma protection - Oertli, Mathias; Sundquist, Malin; Hitzler, Iris; Engler, Daniela B; Arnold, Isabelle C; Reuter, Sebastian; Maxeiner, Joachim; Hansson, Malin; Taube, Christian; Quiding-Järbrink, Marianne; Müller, Anne (The Journal of clinical investigation, 2012)
Persistent colonization with the gastric bacterial pathogen Helicobacter pylori causes gastritis and predisposes infected individuals to gastric cancer. Conversely, it is also linked to protection from allergic, chronic inflammatory, and autoimmune diseases. We demonstrate here that H. pylori inhibits LPS-induced maturation of DCs and reprograms DCs toward a tolerance-promoting phenotype. Our results showed that DCs exposed to H. pylori in vitro or in vivo failed to induce T cell effector functions. Instead, they efficiently induced expression of the forkhead transcription factor FoxP3, the master regulator of Tregs, in naive T cells. Depletion of DCs in mice infected with H. pylori during the neonatal period was sufficient to break H. pylori-specific tolerance. DC depletion resulted in improved control of the infection but also aggravated T cell-driven immunopathology. Consistent with the mouse data, DCs infiltrating the gastric mucosa of human H. pylori carriers exhibited a semimature DC-SIGN(+)HLA-DR(hi)CD80(lo)CD86(lo) phenotype. Mechanistically, the tolerogenic activity of H. pylori-experienced DCs was shown to require IL-18 in vitro and in vivo; DC-derived IL-18 acted directly on T cells to drive their conversion to Tregs. CD4(+)CD25(+) Tregs from infected wild-type mice but not Il18(-/-) or Il18r1(-/-) mice prevented airway inflammation and hyperresponsiveness in an experimental model of asthma. Taken together, our results indicate that tolerogenic reprogramming of DCs ensures the persistence of H. pylori and protects against allergic asthma in a process that requires IL-18.